2019
DOI: 10.1002/lom3.10309
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the diffusive boundary layer thickness above the sediment–water interface in a thermostated rotating‐disk reactor

Abstract: The diffusive boundary layer (DBL) is a thin layer of fluid at the interface with a solid surface in which frictional forces cause molecular diffusion to become the dominant mode of solute transport. The thickness of the DBL is a function of the nature and roughness of sediment substrates, as well as the bottom‐current speed. In low‐energy natural aquatic environments, such as abyssal plains or lakes, the thickness of the DBL can reach several millimeters and significantly impede the diffusive rate of solutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…However, in light of the above, k c should arguably be viewed as an unknown fitting parameter that in some cases reflects not the calcite heterogenous dissolution kinetics but the prevailing mass‐transport conditions. This conclusion that the calcite dissolution kinetics of sediment layers are likely under mass‐transport control has been previously evidenced in the literature and is supported by both laboratory[ 65 , 66 ] and field‐based studies. [67] As early as 1971 Berner [41] reflected that dissolution is usually diffusion controlled and later that decade Morse recognized that mass‐transport may limit the rate of dissolution at the seafloor.…”
Section: From the Laboratory To The Oceansupporting
confidence: 83%
“…However, in light of the above, k c should arguably be viewed as an unknown fitting parameter that in some cases reflects not the calcite heterogenous dissolution kinetics but the prevailing mass‐transport conditions. This conclusion that the calcite dissolution kinetics of sediment layers are likely under mass‐transport control has been previously evidenced in the literature and is supported by both laboratory[ 65 , 66 ] and field‐based studies. [67] As early as 1971 Berner [41] reflected that dissolution is usually diffusion controlled and later that decade Morse recognized that mass‐transport may limit the rate of dissolution at the seafloor.…”
Section: From the Laboratory To The Oceansupporting
confidence: 83%
“…In this type of experiment, a disc, containing the sample, rotates at the base of the reactor and there is no overhead stirrer. The motion of the disc causes the fluid in the chamber to flow in a coherent manner, which is described by a well-defined physico-chemical hydrodynamic model -see Sulpis et al (2019) for particulars on this point. These investigators found that the dissolution rate of such beds remained dependent on the rotation rate for angular velocities up to $20 rps, which is a relatively fast rotation rate.…”
Section: Introductionmentioning
confidence: 99%
“…Benthic oxygen consumption increases as sediments beneath finfish farms become enriched with C (Findlay & Watling 1997, Nickell et al 2003 and thus may be used as an indicator of enrichment (Cathalot et al 2012). However, while the demand for oxygen increases with the concentration of organic matter in the sediments, the supply of oxygen is re stricted by the rate it can be transported across the diffusive boundary layer either by diffusion or through turbulent bursting events (Hondzo 1998, Glud 2008, O'Connor & Hondzo 2008, Grant & Marusic 2011, Sulpis et al 2019. The thickness of this layer, and hence potential rates of transport through this layer, depends on the nature and roughness of the substrate (Dade 1993, Røy et al 2002, but also on the intensity of near-bed turbulence (Hondzo 1998, Lorke et al 2003 and the action of bioturbation and bio-irrigation (Svensson & Leonardson 1996, Pi sched da et al 2008.…”
Section: Introductionmentioning
confidence: 99%